KENDALA DAN PELUANG EKONOMI MONETER ISLAM DI INDONESIA - Jamila, Khaidar Rahmaini; Hutauruk, Muhammad Zaky Abdullah (HUMAN FALAH: Jurnal Ekonomi dan Bisnis Islam, 2024)
AbstractThe Islamic monetary economy in Indonesia shows significant potential for development, especially in the sharia banking sector. Even though Indonesia has the largest Muslim population in the world, the application of sharia principles in macroeconomic policy still faces various obstacles. This research identifies the opportunities and challenges faced by the Islamic monetary economy, including the public's low understanding of Islamic financial products and the dominance of the conventional economic system. Through literature analysis and a thematic approach, this research provides the effectiveness of sharia financial regulation and supervision, as well as providing recommendations for better development. The results of this research indicate that the Islamic monetary economy in Indonesia has great potential to develop, especially in the sharia banking sector. However, there are significant obstacles that need to be overcome, such as the public's lack of understanding about Islamic financial products, the dominance of the conventional economic system, limited access to capital, and challenges in implementing technology. By realizing global awareness of the importance of ethical business practices, Islamic monetary economics is expected to contribute to sustainable and inclusive economic development in Indonesia.